Optimization of Mountainous Communal Spaces for Sustainable Tourism in Gubugklakah - Ramdlani, Subhan; Supriyono, Bambang; Riniwati, Harsuko; Yanuwiadi, Bagyo (Journal of Indonesian Tourism and Development Studies, 2025)
Mountainous regions frequently encounter difficulties in optimising communal spaces for tourism and local requirements due to the presence of topographical and cultural complexities. This study focused on Gubugklakah, East Java, a village renowned for its proximity to Mount Bromo, its rich agricultural heritage, and its Tenggerese cultural identity. The objective was to analyse spatial and activity patterns in communal spaces, addressing issues related to overcrowding, underutilisation, and accessibility, to propose strategies for sustainable tourism. A mixed-method approach was employed, combining spatial analysis using GIS tools, participatory observation of local and tourist activities, and structured community surveys. The analysis of spatial data enabled the mapping of the distribution and accessibility of communal spaces, while the qualitative insights derived from field observations illuminated the socio-cultural dynamics. The surveys collected data from residents and tourists regarding their perspectives on space utilisation and satisfaction. The findings indicated that communal spaces situated in proximity to major attractions, such as marketplaces and cultural sites, frequently experienced high levels of congestion, whereas peripheral areas remained underutilised. The activities of tourists were found to be centred around cultural festivals, agritourism, and recreational pursuits, whereas those of the local population were focused on economic and social interactions. The study identified three key challenges: inadequate infrastructure, limited funding, and the need to strike a balance between tourism development and environmental conservation. The study concluded that adaptive spatial planning, incorporating multifunctional designs and enhanced transportation links, can significantly improve the utility of communal spaces. It also recommended policies emphasising community-based management and sustainable practices to align development with cultural preservation and environmental sustainability. These findings provide actionable insights into optimising communal spaces to foster inclusive tourism growth and local economic resilience.